GET A 12-CHANNEL EKG USING AN AD8232 SINGLE-CHANNEL EKG DEVICE - Jabborov Anvar Mansurjonovich (Web of Journals Publishing, 2023)
EcG instruments measure the electrical activity of the heart muscle to determine the state of the heart. The quality of the ECG signal is a key factor in the detection of heart disease. This work will take a 12-channel EKG of the AD8232 single-channel portable EKG device. This one-channel EKG device with a 12-channel EKG collection technique makes it possible to diagnose the ECG much more conveniently.
Keywords: 12-channel EKG, EKG, QRS, Arduino, Diagnostics, AD8232.